Motnje v postopku hlajenja koruznega zrnja v vertikalnih gravitacijskih sušilnicah - Krička, Tajana (Strojniški vestnik, 2005)
The process of corn-grain drying is usually conducted in such a way that corn grains come into a cooler zone at a moisture level that is 2.0% higher than the equilibrium level. As well as being cooled, the corn grains in the cooler zone also get dried by between 1.5% and 2.0%. However, our research has shown that this is not always the case, since corn grains are sometimes re-hydrated in the cooler zone by 0.65% to 4.26%. Our research also included an analysis of the moisture levels of corn grains in the horizontal section of the cooler zone. Depending on the location, the difference in the moisture levels of the corn grains varied from 1.99% to 4.35%, reaching as much as 10.0% in some extreme cases. This resulted in a higher energy consumption, a decrease in capacity and heterogeneously dried corn grains.
Keywords: rehidracija; cone hladilne; sušenje; zrnje koruzno; zrnje